2012
DOI: 10.1155/2012/374398
|View full text |Cite
|
Sign up to set email alerts
|

Negative Pressure Wound Therapy Literature Review of Efficacy, Cost Effectiveness, and Impact on Patients' Quality of Life in Chronic Wound Management and Its Implementation in the United Kingdom

Abstract: This is a paper reviewing the National Health Service (NHS) agenda in relation to the use of Negative Pressure Wound Therapy (NPWT) in chronic wound management and assesses the evidence behind it, its cost effectiveness and the outcome it has on patients' satisfaction and life style. Multiple studies over the last 10 years looking at clinical efficacy of NPWT with its cost effectiveness and the implementation of this service in the UK were reviewed. NPWT has showed a reasonable body of evidence to support its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 39 publications
(38 reference statements)
0
50
0
3
Order By: Relevance
“…There have been a number of reviews of NPWT [4][5][6][7][8] , with some favouring NPWT over standard dressings [5,6] and others failing to find convincing evidence of benefit [4,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…There have been a number of reviews of NPWT [4][5][6][7][8] , with some favouring NPWT over standard dressings [5,6] and others failing to find convincing evidence of benefit [4,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these focus either primarily or entirely on studies of NPWT in the treatment setting [5][6][7][8], although a Cochrane review of NPWT for prophylactic postoperative use concluded that the evidence for effectiveness was unclear [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in various acute or chronic wounds, others reported better QoL. 30,39 In fact, a true cost analysis was not performed. Wanner, 28 wrote only that NPWT was "cheaper than the traditional dressings".…”
Section: Discussionmentioning
confidence: 99%